Cutting Fertility? The Effect of Cesarean Deliveries on Subsequent Fertility and Maternal Labor Supply - Martin Halla; Harald Mayr; Gerald J. Pruckner; Pilar Garcia-Gomez (Institute for the Study of Labor (IZA), 2016)
The incidence of Cesarean deliveries (CDs) has been on the rise. The procedure's cost and benefits are discussed controversially; in particular, since non-medically indicated cases seem widespread. We study the effect of CDs on subsequent fertility and maternal labor supply. Identification is achieved by exploiting variation in the supply-side's incentives to induce non-medically indicated CDs across weekdays. On weekends and public holidays obstetricians' are less likely to induce CDs (due tighter capacity constraints in hospital). On Fridays and other days preceding a holiday, they face an increased incentive to induce CDs (due to their demand for leisure on non-working days). We use high-quality administrative data from Austria. Women giving birth on different weekdays are pre-treatment observationally identical. Our instrumental variable estimates show that a non-planned CD at parity one decreases life cycle fertility by almost 17 percent. This reduction in fertility translates into a temporary increase in maternal employment.
Keywords: I12; J13; J11; J22; J21; 330; Caesarean delivery; Caesarean section; fertility; female labor supply